The Evolution of Values-Based Education: Bringing Global Insights and Local Practices to a Sustainable Future - Syafika, Wanda; Marwa, Nabilah (Sinergi International Journal of Education, 2024)
This study presents a comprehensive narrative review of Values-Based Education (VBE) and its implementation across diverse global contexts. It aims to explore the effectiveness, challenges, and opportunities of VBE by synthesizing current literature on pedagogical approaches, curriculum design, teacher preparedness, and student outcomes. A systematic methodology was employed, involving searches in Scopus, Google Scholar, ERIC, and JSTOR using targeted keywords related to values-based, moral, and character education. Inclusion criteria focused on peer-reviewed studies from 2000 to 2024 that addressed formal education systems. The findings reveal that VBE enhances student engagement, promotes ethical reasoning, and strengthens character development when integrated into culturally responsive curricula. Effective VBE implementation is closely linked to supportive education policies, professional teacher training, and participatory evaluation mechanisms. Case studies from Indonesia, Finland, and Canada highlight how locally adapted values-based models contribute to improved academic outcomes and social cohesion. Nevertheless, challenges such as inconsistent policy frameworks, lack of teacher preparation, and cultural heterogeneity impede consistent application, especially in developing countries. This review underscores the urgent need for holistic educational reforms that institutionalize values-based learning. It recommends multi-stakeholder collaboration, curriculum innovation, and ongoing teacher development to embed values meaningfully into education systems. Future research should examine long-term impacts and context-specific strategies to optimize the global potential of VBE. These findings affirm that values integration is not only beneficial but essential for cultivating ethical and engaged citizens in an increasingly complex world.